International perspectives on leadership in higher education. vol. 15 - Blair, Alasdair; Evans, Darrell; Hughes, Christina; Tight, Malcolm (International perspectives on higher education research ;, 2022)
As complex, large institutions, universities present unique challenges for leaders. What is the nature of leadership for the 21st century? Should universities continue to rely predominantly on recruiting from within or should university leaders be drawn from wider professional fields and industries? How should such leaders be developed and supported? What does the existing research tell us about all of these questions, and what further research needs to be done? International Perspectives on Leadership in Higher Education examines how contemporary leaders in higher education - in different disciplines, at different levels and in different parts of the world - are identified, developed and supported. Employing a mixture of theoretical, practical and personal perspectives, it shows how notions and expectations of leadership in higher education are changing, discusses the varied reasons behind these trends, and speculates on possible future developments. International Perspectives on Leadership in Higher Education is essential reading for new and aspiring leaders in higher education worldwide, as well as for those responsible for selecting and supporting leaders to thrive in a higher education environment.